Structural aspects of the phase and texture formation processes in thin-layer Ni-W/TiN systems which are perspective for creating high-temperature superconductors of the second generation - Sunhurov, M.S.; Derevyanko, V.V.; Leonov, S.A.; Sukhareva, T.V.; Finkel, V.A.; Shakhov, Yu.N. (Functional Materials, 2017)
The investigation objective is searching for the new ways of controlling the structural properties of paramagnetic substrates for creating the high temperature coated superconductors for power applications. Processes of the texture formation in two-component Ni-W/TiN system is studied for paramagnetic Ni - 9.5 at. % W tape with TiN coating, which is deposited by ion-plasma deposition of Ti in nitrogen atmosphere. It is investigated by means of XRD analysis the influence of the deposition time and pressure of nitrogen on the phase and cubic texture formation in the both subsystems of Ni - 9.5 at. % W/TiN. It is found the effect of the crystal planes reorienting in the tape of Ni - 9.5 at. % W under the influence of TiN coating, that leads to a substantial strengthening of the cubic texture of the metallic ribbon. It is also observed the difference in the mechanism of coating formation during the deposition of TiN on the front and the back(shady) side of the substrate. It is also revealed that optimization of the conditions of thin TiN layer deposition makes it possible to obtain quasi single crystalline TiN coatings with a cubic texture. These textured Ni - 9.5 at. % W/TiN substrates admit the epitaxial growth of the high quality HTS films with high current carrying capacity.